2006
DOI: 10.1021/jp061563l
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ultraviolet Emission from ZnS-Coated ZnO Nanowires Fabricated by Self-Assembling Method

Abstract: A simple chemical route for ZnS-coated ZnO nanowires with preferential (002) orientation is reported. Sodium sulfide and zinc nitrate were employed to supply S and Zn atoms at 60 degrees C to form ZnS-coated ZnO nanowires structures. Electron diffraction measurement shows that the ZnO/ZnS core-shell nanostructure is single crystalline. Interesting features are found in the photoluminescence (PL) spectra of ZnS-coated ZnO nanostructures. After coating, the UV emission of nanorods is dramatically enhanced at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 20 publications
4
87
0
Order By: Relevance
“…Even though there is a great interest in the photoluminescence (PL) properties of one-dimensional (1D) ZnS nanostructures, few studies are available in the literature on possible UV emission at room temperature. The reported UV emissions from ZnS are at 365 [11], 322 [12], 333 [13], 375 [14], 374 [15], and 380 nm [16], and these are have fewer applications in device fabrication because of the feeble emission nature. Enhanced optical properties of ZnS nanocrystals are also obtained by using capping agents and surfactants like trioctylphosphine oxide (TOPO) [17], chitosan [18], trioctylphosphine oxide [19], ethylenediamine, dodecylthiol [20], 1-ethyl-3-methylimidazolium ethyl sulphate [21], and didecyldimethylammonium bromide (DDAB) [22] during the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is a great interest in the photoluminescence (PL) properties of one-dimensional (1D) ZnS nanostructures, few studies are available in the literature on possible UV emission at room temperature. The reported UV emissions from ZnS are at 365 [11], 322 [12], 333 [13], 375 [14], 374 [15], and 380 nm [16], and these are have fewer applications in device fabrication because of the feeble emission nature. Enhanced optical properties of ZnS nanocrystals are also obtained by using capping agents and surfactants like trioctylphosphine oxide (TOPO) [17], chitosan [18], trioctylphosphine oxide [19], ethylenediamine, dodecylthiol [20], 1-ethyl-3-methylimidazolium ethyl sulphate [21], and didecyldimethylammonium bromide (DDAB) [22] during the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…ZnS is having higher bandgap than that of ZnO, a suitable candidate material for shell coating. There were few reports available about the formation of core-shell structure by using H 2 S and Na 2 S [6,8]. Figure 3 shows the TEM photograph of ZnO-ZnS core-shell structure having a thin layer of ZnS nanostructures around ZnO particles.…”
Section: Resultsmentioning
confidence: 99%
“…2.2 Preparation of core-shell structure A simple chemical synthesis procedure was applied to prepare ZnS shell structure on the surface of the ZnO nanoparticles followed by [6]. About 0.81 g/l of ZnO dispersion was taken.…”
Section: Experiments 21 Preparation Of Nanoparticlesmentioning
confidence: 99%
“…16 Of these techniques, formation of core-shell nanostructures by encapsulating ZnO nanostructures with other semiconducting oxide thin films has been reported by many research groups. [17][18][19][20][21][22][23][24][25][26] Recently, we reported that ultraintense shortwavelength emission could be obtained from ZnO-sheathed MgO nanorods induced by subwavelength optical resonance cavity formation. 27 This technique differs from previous encapsulation techniques in that the core and shell materials were MgO and ZnO, respectively.…”
Section: -12mentioning
confidence: 99%